PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK - Mahareny, Mutya Sakina; Wijayanti, Anita; W, Endang Masitoh (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Tax avoidance can lead to loss of reputation and corporate image, and a decline in stock prices (Kim and Chae, 2016: 284). The purpose of this research is to know the influence of independent commissioner, audit committee and audit quality to tax avoidance (Empirical Study on Consumer Goods Industry Sector Listed on Indonesia Stock Exchange Period 2012-2016). This research is a quantitative research with kind of causal associative research. The research population is all of the entire consumer goods industry sector listed in Indonesia Stock Exchange period 2012-2016, which is 24 companies. Sampling technique using purposive sampling. Companies that have met the criteria are as many as 22 companies, so the data obtained as much as 110 data. The classical assumption test uses normality test, multicollinearity, autocorrelation and heteroscedasticity. Data analysis technique using Multiple Linear Regression, F test, t test and coefficient of determination (R2). The results of multiple linear regression analysis indicate that independent commissioners, audit committee and audit quality simultaneously have significant effect on tax evasion (Empirical Study on Consumer Goods Industry Sector Listed in Indonesia Stock Exchange Period 2012-2016). Partially indicates that Independent Commissioners have a significant effect on tax evasion. Audit Committee has a significant effect on tax evasion. Audit quality has no significant effect on tax evasion. R Square value of 0.288. This indicates that the independent commissioner's variables, audit committee and audit quality have contributed (can explain) the effect on tax evasion variable of 28.8%. While the rest of 71.2% received contributions from other variables outside the study, namely information transparency, firm size, profitability, fiscal loss compensation, leverage, and financial ratios.